Amandemen Pasal 33 UUD 1945 Yang Dipaksakan - Mubyarto - (Universitas Islam Indonesia, 2003)
The founding fathers of the country have built economic system which contains vision and mission to ensure the prosperity for the people. The problem that occur in the past, the system didn't work because the government and some intellectuals forgot this honorable vision and mission for the sake of the pragmatism mind frame. Therefore, the most important thing is how to create appropriate an amendment for constitution which can certainly prevent the violation and the 'moral hazard' actions toward national economy and guarantee not to change spirit that embodied with its chapters.